Semiotika Iklan Politik “Makan Siang dan Susu Gratis serta Nutrisi” dalam YouTube Kandidat Prabowo-Gibran - Permatasari, Julia; Sunarto, Sunarto (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The political advertisement titled "Free Lunch and Milk Program with Nutrition" represents a modern political communication strategy that relies on visual signs to shape public opinion. This analysis employs Charles Sanders Peirce’s semiotic theory to explore the meanings behind the signs presented in the advertisement. A qualitative approach is applied through semiotic analysis of content uploaded on the YouTube platform, focusing on the relationship between representamen, object, and interpretant in the construction of political messages. The analysis reveals that the advertisement builds a positive image through signs that represent concern for children's nutrition. These findings reinforce the relevance of Peirce’s semiotic theory in understanding contemporary political communication strategies and offer a conceptual contribution to the study of visual communication in digital media.